Impact of intravenous immunoglobulin treatment on peripheral blood cells in children with Kawasaki disease complicated with coronary artery lesion - Junshan Zhao; Yingying Ma; Li Xin; Lijun Wang; Hongliang Gao (Italian Journal of Pediatrics)
Abstract Background Kawasaki disease (KD) primarily affects young children and can lead to coronary artery lesions. Intravenous immunoglobulin (IVIG) treatment is essential; however, it may fail in 10-20% of cases, increasing the risk of complications. Complete blood count (CBC) tests can help assess disease severity and predict risks. This study investigated the impact of IVIG on peripheral blood cells, including neutrophil count, platelet-lymphocyte ratio, hemoglobin level, mean platelet volume (MPV), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP), in children with KD complicated by coronary artery lesions (CALs). Methods This retrospective analysis included children diagnosed with typical KD. The neutrophil count, hemoglobin level, platelet-lymphocyte ratio, MPV, ESR, and CRP were compared between those with (CAL+) and without (CAL−) CALs during the acute phase, as well as at 7 days, 1 month, and 2 months after normalizing body temperature with IVIG. Results A total of 76 children with KD were analyzed, including 30 with CAL+. CAL+ and CAL− patients exhibited elevated neutrophil counts during the acute phase, with no significant differences (P > 0.05) between groups. After IVIG treatment, CAL− patients demonstrated a more pronounced reduction in neutrophil count (P < 0.05) than CAL+ patients. Hemoglobin levels differed significantly during the acute phase (P < 0.05) but were comparable post-treatment (P > 0.05) between CAL+ and CAL− patients. The platelet-lymphocyte ratio varied significantly between groups during the acute phase and 1-month post-treatment (P < 0.05). Mean ESR and CRP levels were significantly elevated at all time points in the CAL+ group compared with the CAL− group. No significant differences in MPV were observed between groups. Conclusions After IVIG treatment, CAL− patients demonstrated a more important reduction in neutrophil count than CAL+ patients after IVIG. Pediatric patients with KD and CAL+ showed lower hemoglobin and platelet-lymphocyte ratio and higher ESR and CRP compared with CAL−, suggesting that they may serve as indicators for CAL in pediatric patients with KD.